Immunoproteasome Inhibition Impairs Differentiation but Not Survival of T Helper 17 Cells - Franziska Oliveri; Dennis Mink; Tony Muchamuel; Michael Basler (Cells)
Autoimmune and inflammatory diseases are characterized by aberrant immune responses. The immunoproteasome was proposed as a target for such Th cell-mediated diseases due to its role in the activation, differentiation and function of T cells. Even though many studies demonstrated reductions in Th17 cells upon immunoproteasome inhibition, it is still unclear if the differentiation or survival of these cells is affected. Therefore, this study used DSS-induced colitis and house dust mite airway inflammation mouse models to investigate the effect of immunoproteasome inhibition on Th17 cells and Tregs at different time points. Th17 cells were almost abolished when immunoproteasome inhibition was applied continuously in DSS-induced colitis. In contrast, immunoproteasome inhibition did not decrease levels of already differentiated Th17 cells and did not enhance Treg induction. Dendritic cells were barely affected by immunoproteasome inhibition. Moreover, immunoproteasome inhibition reduced T cell activation in vitro and in vivo, suggesting impaired activation as the underlying mechanism for reduced Th17 differentiation. In conclusion, immunoproteasome inhibition reduces Th17 differentiation by impairing the activation of naïve T cells, but it does not affect the survival of already-differentiated Th17 cells and Tregs.